Profit-Loss Sharing Contract as an Alternative to Solve Unemployment in Sudan through Investment in Livestock Breeding - Mahmoud Mohamed Ali Mahmoud Edris; Mohamed Sharif Bashir; Yusuf Sani Abubakar (Research Center of State Institute for Islamic Studies (IAIN) Kudus, 2024)
Vol 17, No 2